2007
DOI: 10.1097/yct.0b013e318065b12f
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy Use in Pregnancy

Abstract: Treatment of psychiatric disorders during pregnancy poses many challenges. Electroconvulsive therapy is a relatively safe and effective treatment during pregnancy if steps are taken to decrease potential risks. In this article, we discuss premature labor in a patient who underwent electroconvulsive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 5 publications
0
12
0
7
Order By: Relevance
“…Fetal bradyarrhythmia is the most common problem in the fetus caused by ECT [ A change of anesthetic agent from methohexital to propofol attenuated the seizure duration resulting in the elimination of further events of fetal cardiac deceleration and a successful outcome for both mother and fetus [81] Gahr et al to rTMS [82] Salzbrenner et al [85] O'Reardon et al Mother: cesarean delivery Fetus: no complications ECT was effective and safe for treating severe major depression during pregnancy [86] Pesiridou et al ECT during the third trimester of pregnancy may be delayed. Patients and treatment team need to be aware of this possibility, particularly when ECT is conducted on an outpatient basis [87] Ghanizadeh et al Ceccaldi et al [90] Pinette et al ECT is effective and safe [94] DeBattista et al Fukuchi et al Inhalation anesthesia is beneficial for ECT in the last stage of pregnancy to reduce uterine contractions caused by potential uterine relaxation effect of anesthetics [97] Bhatia et al ECT during pregnancy improves maternal condition and does not adversely affect fetal wellbeing [102] Sherer et al Mother: no complications Fetus: no complications ECT was highly effective and careful monitoring of both the mother and the fetus demonstrated that this was a safe procedure [103] Griffiths et al Transient fetal heart rate decreases probably result mainly from hypoxia [68]. The electroconvulsive current does not pass through the uterus [69,70], and so other physiological and pathophysiological factors have to be considered as causes for this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal bradyarrhythmia is the most common problem in the fetus caused by ECT [ A change of anesthetic agent from methohexital to propofol attenuated the seizure duration resulting in the elimination of further events of fetal cardiac deceleration and a successful outcome for both mother and fetus [81] Gahr et al to rTMS [82] Salzbrenner et al [85] O'Reardon et al Mother: cesarean delivery Fetus: no complications ECT was effective and safe for treating severe major depression during pregnancy [86] Pesiridou et al ECT during the third trimester of pregnancy may be delayed. Patients and treatment team need to be aware of this possibility, particularly when ECT is conducted on an outpatient basis [87] Ghanizadeh et al Ceccaldi et al [90] Pinette et al ECT is effective and safe [94] DeBattista et al Fukuchi et al Inhalation anesthesia is beneficial for ECT in the last stage of pregnancy to reduce uterine contractions caused by potential uterine relaxation effect of anesthetics [97] Bhatia et al ECT during pregnancy improves maternal condition and does not adversely affect fetal wellbeing [102] Sherer et al Mother: no complications Fetus: no complications ECT was highly effective and careful monitoring of both the mother and the fetus demonstrated that this was a safe procedure [103] Griffiths et al Transient fetal heart rate decreases probably result mainly from hypoxia [68]. The electroconvulsive current does not pass through the uterus [69,70], and so other physiological and pathophysiological factors have to be considered as causes for this problem.…”
Section: Discussionmentioning
confidence: 99%
“…The complications included status epilepticus (63), hematuria (28), miscarriage (13,54), uterine contractions and/or preterm labor (21,25,34,39,48,55,57,58,67), vaginal bleeding (25,28), abdominal pain (39), and placental abruption (50). Both miscarriages were believed to be unrelated to ECT: one was a miscarriage after an MVA (13), and the other was preterm labor 8.5 weeks after the last ECT treatment (54).…”
Section: Maternal Adverse Effectsmentioning
confidence: 96%
“…Her ne kadar bu fötal kardiyak aritmilerin geçici olduğu bildirilse de EKT uygulamalarında fötal kardiyak monitörizasyon önerilmektedir. 20 Fakat fötal kardiyak monitörizasyondaki teknik zorluklar ve olgumuzun 16 haftalık gebe olması nedeniyle yapılamamıştır. Bu sebeble her EKT seansı öncesi ve sonrası hasta derlendikten sonra USG ile fötal kardiyak aktivite ve hareketler obstetrisyen tarafından değerlendirilmiş ve herhangi bir sorun tespit edilmemiştir.…”
Section: Discussionunclassified